Effects of deltamethrin on antioxidant status and oxidative stress biomarkers in freshwater mussel, Unio elongatulus eucirrus - Koprucu, S. Simsek; Yonar, E.; Seker, E. (Springer, 2008)
In this study, the effects of deltamethrin on antioxidant status and oxidative stress biomarkers in digestive gland and gill of freshwater mussel, Unio elongatulus eucirrus, was examined. Deltamethrin was applied at concentrations of 25, 50, 100, 200, 400, 800 and 1,600 mu g L-1, for 1, 24, 48, 72 and 96 h. With increasing deltamethrin concentrations, the mussels exposed duration 1-96 h significantly increased lipid peroxidation, which might be associated to decreased levels of reduced glutathione and catalase activity in digestive gland and gill of freshwater mussel (p < 0.05 for each cases). Negative correlations were observed between the lipid peroxidation and glutathione or catalase levels after deltamethrin exposure, indicating a protective role of glutathione and catalase against lipid peroxidation, suggesting the use of these antioxidants as a potential biomarker of toxicity associated with contaminant exposure in freshwater mussels.
Keywords: freshwater mussel; Unio elongatulus eucirrus; deltamethrin; oxidative stress; antioxidants; biomarkers